Agricultural credit access and utilization in Myanmar’s dry zone - Htun, Khun Moe; Tin, Myat Su (Michigan State University, 2017)
This research highlight presents findings on access to and use of agricultural credit by farm households in Myanmar’s Central Dry Zone. Data was collected by the Rural Economy Agriculture Dry Zone Survey (READZ). READZ was implemented during March to May 2017 with 1578 rural households in the townships of Budalin, Myittha, Magway and Pwinbyu. Results presented here are based on responses from a subsample of 1066 households engaged in agriculture. We analyze access to, terms and utilization of agricultural loans from the Myanmar Agricultural Development Bank (MADB) and other sources over the 12 months preceding the survey. For our analysis, farm households were ranked by area of agricultural land owned, and divided into three equal groups. The smallest third of farms is referred to as agricultural landholding tercile 1 and the largest as tercile 3.